Theoretical Investigation of Structural and Electronic Properties of Ruthenium Azopyridine Complexes Dyes for Photovoltaic Applications by Using DFT and TD-DFT Methods - Nâ€™guessan, Nobel Kouakou; Bamba, Kafoumba; Patrice, Ouattara Wawohinlin; Ziao, NahossÃ© (European Scientific Journal, ESJ, 2018)
In this work, a series of ruthenium azopyridine complexes was studied theoretically as a sensitizer in Dye Sensitized Solar Cells (DSSCs) using density functional theory (DFT) and time-dependent DFT (TD-DFT). These dyes derive from ruthenium azopyridine complex RuCl2(Azpy)2 considered as the reference by grafting an anchoring group (-COOH). Hens, 4-Hmazpy, 5-Hmazpy and O-Hazpy ligands as well as Azpy were studied. For the four ligands, 20 isomers expected are studied. In order to explore their photoelectrical properties, the ground state and excited state properties of the isolated dyes have been calculated at B3LYP/LANL2DZ level. And the same work was done with the dye RuCl2(5Hmazpy)2 in interaction with titanium dioxide. Comparing to N3, the key parameters including the light harvesting efficiency (LHE), the electron injection driving force Î”Ginject , the regeneration driving force Î”Gregen , the open circuit voltage VOC, the life time Ï„ and adsorption energy were all scrutinized in detail. It results from this calculation that the ruthenium azopyridine complexes can be used as sensitizer in DSSCs. This work has highlighted the predictive and the guiding role of the theoretical approach in the design and the conception of new dyes for solar cells.